“Estimación del índice de mérito total del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia Tanicuchí” - Acosta Salazar, Paola Nicoll (2023)
In the province of Cotopaxi, there is a need for a genetic improvement project in milk producing cattle, which are assessed animals phenotypic and genetic data, due to the production is inefficient. The current research was made in the Tanicuchí parish from Latacunga canton, where it found small and medium producers dedicated to the milk production and commercialization. It collected data (genealogical information, production costs, daily weight gain, milk production and density) and finding the producers main problems; this allowed to determine the aims of genetic improvement as the response to selection, in order to get superior animals. For assessing the economic value, it was a production costs statistical analysis and was used the BLUP method to estimate the genetic value and the response to selection. The got results showed, what the milk production costs per liter average monthly price is $0.15 cents and the average monthly profit is $1472.30. The largest expense generated is for food, with a monthly average $354.99, which corresponds to total expenditure 44%. The response to selection for daily weight gain averaged 156.07 g/day, for archieving the estimated value (700 g/day) are needed four generations; for milk production the average is 2107.82 kg/lactation to get the estimated value (5000 kg/lactation), it is needed nine generations; and for milk density the average was 1.025 g/ml to reach the estimated value (1.032 g/ml) it is needed one generation. These data provide a significant contribution for producers, which contributes to a more profitable and sustainable dairy operation.